Development and Validation of Augmented Reality Media for Social and Emotional Learning in Children with Learning Disabilities (SEAKAR) - Redydian Adhitya Nugraha; Sunardi Sunardi; Asrowi Asrowi; Tri Murwaningsih; Munawir Yusuf; Mahardika Supratiwi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learning disabilities (LD) are neurological conditions that affect brain function, often resulting in challenges with reading, writing, and mathematics, despite individuals typically having average or above-average intelligence. Students with LD frequently experience socio-emotional difficulties, such as anxiety and social rejection, which can hinder academic progress and self-esteem. Building resilience is essential to help these students cope with stress and adapt to challenges. This study aimed to develop an educational tool titled Collaborative Social-Emotional-Academic Augmented Reality (SEAKAR) to support students with LD in inclusive school settings. The tool was designed using the CASEL (Collaborative for Academic, Social, and Emotional Learning) framework and integrated with augmented reality (AR) technology. A Research and Development (RD) approach was employed, consisting of a needs assessment, prototype creation, expert validation, and iterative revisions. Ten expert validators—comprising specialists in special education, psychology, language, media, ICT, and inclusive education—assessed the SEAKAR prototype. Feedback from the validation process was positive, indicating the product’s relevance, functionality, and potential effectiveness in supporting the social-emotional and academic needs of students with LD. The development of SEAKAR represents a promising step toward innovative, inclusive educational tools that integrate social-emotional learning with technology. Its alignment with the CASEL framework and use of AR enhances its potential to engage and support students with LD. Further implementation and testing in real classroom settings are recommended to evaluate its practical impact.